2009
DOI: 10.2172/951802
|View full text |Cite
|
Sign up to set email alerts
|

Wind-To-Hydrogen Project: Operational Experience, Performance Testing, and Systems Integration

Abstract: AcknowledgmentsThe authors would like to recognize Rick Farmer, Roxanne Garland, and Jamie Holladay of the U.S. Department of Energy for funding this work. George Sverdrup of the National Renewable Energy Laboratory (NREL) and Vicki McCarl of Xcel Energy were both very helpful in scoping and defining the Wind2H2 project and have provided excellent feedback throughout the project. Brad Hollenbaugh and Curtis Perry of Xcel Energy were instrumental in helping design and configure the Wind2H2 system and in partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 0 publications
0
46
0
1
Order By: Relevance
“…during daylight, when the wind blows) while consumers expect to have access to electricity available at all times. On the other hand, it is necessary to recognise the scale of operations that is being discussed [13,21]. Table 1 compares the possible size of water electrolysis plants for various applications and compares it with some existing technology.…”
Section: Scaling Our Thinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…during daylight, when the wind blows) while consumers expect to have access to electricity available at all times. On the other hand, it is necessary to recognise the scale of operations that is being discussed [13,21]. Table 1 compares the possible size of water electrolysis plants for various applications and compares it with some existing technology.…”
Section: Scaling Our Thinkingmentioning
confidence: 99%
“…The US National Renewable Energy Laboratory regularly reviews the economics of hydrogen production by water electrolysis and considers issues such as the integration of an electrolysis plant with a wind farm, for example [13,21]. It has been shown clearly that for small systems, the dominant factor in determining the cost of H 2 is the cost of the electrolysis cells while, in contrast, for large systems the cost of electricity and the value of the hydrogen dominate the discussion.…”
Section: à2mentioning
confidence: 99%
“…Through a number of installations of domestic fuel cell (FC) micro-combined heat and power systems (micro-CHPs), the need for heat and electricity from each household is met individually, resulting in 100% carbon neutral. Other applications for utilizing this kind of hydrogen solution to facilitate renewable integration can also be found in [7,8]. The installed capacity of these real-life applications are typically below 100 kW.…”
Section: Introductionmentioning
confidence: 99%
“…In order to verify the PEM electrolyzer model, experimental data from a 6.5 kW (135 A rated, stack voltage ¼ 48 V) PEM electrolyzer stack from NREL's Wind-to-Hydrogen Project were obtained [17]. The electrolyzer model verification can be found in our previous paper [8].…”
Section: Pem Electrolyzer Modelmentioning
confidence: 99%
“…The study determined the exergy efficiency of the various components of the system, and calculated the exergy losses that occurred as a result of irreversibility. Harrison et al [17] reported the design, installation, and operation of the Wind-toHydrogen (Wind2H2) project, in which hydrogen is produced directly from renewable energy sources. This project used solar and wind energy to produce and store hydrogen.…”
Section: Introductionmentioning
confidence: 99%